The Development of Lectora Inspire Media Based on Jombang Local Culture for Fourth Grade Elementary School - Debiya, Lenon; Asmarani, Ratih (IJPSE : Indonesian Journal of Primary Science Education, 2021)
Process in SD level requires learning media to attract students' enthusiasm for learning. activities in classroom can follow the development without reducing moral education and student creativity. Introduction of local culture is necessary in the learning process so that students can understand the culture around them. This study to determine the development of media by Lectora inspire with cultural in country for the fourth grade of SD, and to find the quality of media in learning SD. This research was carried out at SD Kepanjen 2 Jombang in May 2020/2021 using R&D (Research and Development) but refers to design of ADDIE and its acronym is Analyze, Design, Development, Implementation, and Evaluation. The subjects of the media trial were 20 from class IV-A SD Kepanjen 2 Jombang. The research instrument used a validation sheet and questionnaire with quantitative data analysis techniques and qualitative data. The results of the study in validity percentage is 94.775%. (very valid also worthy of use without improvement), with each material expert rating of 91.55% (very valid also eligible to be used without improvement), and media experts of 98% (very valid also eligible to be used without improvement). The product trial from students obtained an overall percentage assessment of 90.45% (very interesting), while the educator's assessment of 91.7% Lectora inspire-assisted learning media was very interesting and very suitable for use in elementary learning. So it can be concluded that the interactive media developed is very valid and can also be used in learning.